2017
DOI: 10.18632/oncotarget.18864
|View full text |Cite
|
Sign up to set email alerts
|

Low dose of dexmedetomidine as an adjuvant to bupivacaine in cesarean surgery provides better intraoperative somato-visceral sensory block characteristics and postoperative analgesia

Abstract: ObjectIn this study, we aimed to investigate the beneficial effects of dexmedetomidine on somato-visceral sensory block characteristcs, postoperative analgesia and stress response of intrathecal bupivacaine administration in women undergoing cesarean section, and to find out which dose is better.MethodsSixty parturients with the American Society of Anesthesiologists (ASA) physical status I or II were anesthetized with intrathecal bupivacaine(10mg) alone or in combination with dexmedetomidine (3 μg and 5 μg) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 35 publications
1
35
0
Order By: Relevance
“…1 People's Hospital (Jining, China). The effect of dexmedetomidine on visceral pain has also been demonstrated with epidural administration for labor analgesia (12) and with intrathecal administration for cesarean section (31). The similar sensory level at 20 min post-injection indicated that the addition of epidural dexmedetomidine may not affect the cephalad spread of ropivacaine, which was partly supported by Yousef et al (1) and Hanoura et al (2), who reported that epidural dexmedetomidine did not significantly reduce the time to onset of sensory and motor blockade, the time to reach the highest level of sensory block or the time to readiness for surgery, when combined with intrathecal bupivacaine, epidural bupivacaine and fentanyl.…”
Section: Discussionmentioning
confidence: 99%
“…1 People's Hospital (Jining, China). The effect of dexmedetomidine on visceral pain has also been demonstrated with epidural administration for labor analgesia (12) and with intrathecal administration for cesarean section (31). The similar sensory level at 20 min post-injection indicated that the addition of epidural dexmedetomidine may not affect the cephalad spread of ropivacaine, which was partly supported by Yousef et al (1) and Hanoura et al (2), who reported that epidural dexmedetomidine did not significantly reduce the time to onset of sensory and motor blockade, the time to reach the highest level of sensory block or the time to readiness for surgery, when combined with intrathecal bupivacaine, epidural bupivacaine and fentanyl.…”
Section: Discussionmentioning
confidence: 99%
“…But intrathecal opioids will increase nausea and vomiting (Weigl et al, 2017) and itching (Sun et al, 2001;Chen et al, 2010;Sun et al, 2017) that is an uncomfortable experience and prolong the recovery for the parturients after the surgery. Intrathecal dexmedetomidine, an a 2 -adrenergic receptor agonist used as an adjuvant to bupivacaine, has been found to provide better intraoperative nerve blockade than bupivacaine alone as well as prolong postoperative analgesia and alleviate shivering in patients undergoing cesarean section (Bi et al, 2017;He et al, 2017;Xia et al, 2018;Liu et al, 2019). And this minimal dose of intrathecal dexmedetomidine after absorbed into blood and metabolized by the liver may not cause potential fetal toxicity based on the previous studies (Bi et al, 2017;He et al, 2017;Xia et al, 2018;Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 95%
“…Intrathecal dexmedetomidine, an a 2 -adrenergic receptor agonist used as an adjuvant to bupivacaine, has been found to provide better intraoperative nerve blockade than bupivacaine alone as well as prolong postoperative analgesia and alleviate shivering in patients undergoing cesarean section (Bi et al, 2017;He et al, 2017;Xia et al, 2018;Liu et al, 2019). And this minimal dose of intrathecal dexmedetomidine after absorbed into blood and metabolized by the liver may not cause potential fetal toxicity based on the previous studies (Bi et al, 2017;He et al, 2017;Xia et al, 2018;Liu et al, 2019). Zhou et al found that dexmedetomidine can reduce the traumatic stress response and immune suppression caused by surgery and has a protective effect on the spinal cord in spinal surgery (Zhou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Bi et al (2017) all critical appraisal questions were scored "yes" except for one that asked if all the participants who entered the trial were accounted for at its conclusion. During the study if spinal anesthesia failed, participants would be excluded.…”
Section: Critical Appraisalmentioning
confidence: 99%